Evaluating the effect of probiotic supplementation in the form of mouthwash along with scaling and root planing on periodontal indices in patients with stage III and grade A generalized periodontitis: A randomized clinical trial - Shima Ghasemi; Amir Reza Babaloo; Behnam Mohammadi; Mahdieh Esmailzadeh (Tabriz University of Medical Sciences, 2020)
Background. Periodontal disease is a chronic polymicrobial infectious condition. Non-surgical treatments, including scaling and root planing (SRP) with or without adjunctive treatments, are among the recommended treatment options for this condition. This study investigated the effect of probiotic supplementation in the form of mouthwash with SRP on periodontal indices in patients with stage III grade A generalized periodontitis. Methods. Thirty-six patients were randomly assigned to two groups (n=18) and received SRP treatment along with a placebo in one group and probiotic supplementation in the other. After SRP, the test group used daily probiotics for 20 days. The control group subjects were treated only with SRP and placebo mouthwash. Periodontal indices were determined at three time intervals: at baseline and after one and three months. The data were analyzed using SPSS 17. P<0.05 was considered statistically significantd. Results. There were significant differences in BOP levels in both the test and control groups between different intervals, with no significant difference between the groups. The significance of changes in the CAL and PI indices were similar to those in BOP. There were significant differences in PD levels between the groups after one and three months using the mouthwash. There were also significant differences between the PD values at different intervals in both groups. Conclusion. This study's results showed that probiotic supplementation as a mouthwash, along with SRP, had a positive effect on periodontal indices in patients with stage III and grade A generalized periodontitis.